Factors associated with return to work in men and women with work-related traumatic brain injury. Issue 3 (July 2016) - Xiong, Chen; Martin, Tickalyn; Sravanapudi, Aneesha; Colantonio, Angela; Mollayeva, Tatyana
Abstract: Background: Symptoms that persist subsequent to a work-related traumatic brain injury (wrTBI) influence the ability to return to work (RTW) and indicate areas of functional disability, as classified in the International Classification of Functioning, Disability and Health (ICF) framework. Objective: The purpose of this study was to describe the relationship between RTW status and ICF framework domains in men and women with a wrTBI. Methods: A retrospective chart review of 209 consecutive workers with TBI (mild TBI: 71.8%; mean age: 40.2 ± 11.1, men: 71.3%) was conducted. Workers were assessed during the chronic post-injury phase, at the neurology service of a large rehabilitation hospital in Ontario, Canada in 2003. Frequency distributions were calculated and chi-square tests performed. Results: At the point of assessment, 78.0% of workers were in receipt of disability benefits, while the remainder had returned to work on a full- or part-time basis. Significant differences were observed in the Body Functions and Structures domain of the ICF model, specifically clinical diagnoses of depression, anxiety, pain disorders; self-perceived cognitive disturbance, and certain psychosocial factors ( p  < 0.05), between workers who had returned to work and those who had not. When stratified according to sex, these associations remained significant only in men. Conclusions: The factors outlined above should be subject to further TBI research, as indicators for RTW. The lack of significant findings in women warrants further exploration of variables within the physical and social environmental domains of the ICF.